(untitled) (Africa Development, 1989)
Given ils technological, economic and political repercussions, civil aviation is a crucial link in the chain of modern economies. Thus deregulation of commercial aviation has a significant impact on the relationship between the state and the economy and reopens a major debate in Africa. Deregulation coincided with a very specific phase in air transport industry, a phase in which the most significant technological progress has reached its peak. In Africa, however, the last decade has meant a slight decrease in the share of regural African air traffic and an alarming decrease in freight. The problems faced by African airlines are numerous and include, high average age of the fleet, inability to fulfill the newly imposed acoustic norms, higher unit operational costs, higher cost of fuel, maintenance and insurances as well as political interference in management. These problems of air transport in sub-saharan Africa are closely linked to the overall economic and social degradation resulting from the current crisis. Furthermore, the setting up of a united European market will have significant implications for African Airlines. Deregulation of the air transport in this phase of the globalization of the industry has been accompanied by privatization and regrouping. The predominant tendency is toward the formation of multi-mega carriers. In this context options for Africa are limited to "cooperate or die". Following an uncontrolled liberalization policy would mean becoming branches of major European American or Asian airline companies. The alternative is regrouping for survival and development. African airlines could opt to regroup in order to regulate and develop African air transport. For Africa, the urgent agenda is to improve its regulation towards foreign countries and airlines and to liberalize at the African level.